Gel-Infused Translabial Ultrasound in the Evaluation of Female Urethral Stricture. Issue 12 (December 2020) - Sussman, Rachael D.; Kozirovsky, Mariana; Telegrafi, Shpetim; Peyronnet, Benoit; Palmerola, Ricardo; Smilen, Scott; Pape, Dominique M.; Rosenblum, Nirit; Nitti, Victor W.; Brucker, Benjamin M.
Abstract : Objectives: The aims of this study were to describe our technique of gel-infused translabial ultrasound (GITLUS) to assess the female urethra for stricture and to highlight its utility when compared with other diagnostic techniques. Methods: Consecutive patients presenting with prior diagnosis and/or suspicion for female urethral stricture underwent evaluation with uroflowmetry, postvoid residual, video urodynamics, and cystoscopy at the surgeon's discretion. All patients underwent GITLUS; 8-MHz curvilinear and 6-MHz linear high-frequency transducers were used to image the urethra from meatus to bladder neck while instilling 20 mL of lidocaine jelly to distend the urethra. Stricture location, length, caliber, and presence of periurethral fibrosis were assessed. Two healthy volunteers underwent GITLUS to serve as a comparison. Results: Eight patients with suspected stricture underwent GITLUS. In all cases, GITLUS identified and characterized stricture and demonstrated periurethral fibrosis. Two healthy volunteers underwent GITLUS, which demonstrated a patent urethra and no evidence of fibrosis. Cystoscopy and video urodynamics on patients with stricture did not perform as well at identifying and fully assessing strictures. Six patients underwent definitive surgical repair, and GITLUS findings were confirmed. One patient had a postoperative GITLUS demonstrating resolution of the stricture and periurethral fibrosis. Conclusions: Gel-infused translabial ultrasound is a novel and accurate technique that in this small series appeared to identify and further characterize female urethral stricture in cases where it was utilized. Further research is needed to determine its role in preoperative planning and in providing a definitive diagnosis of stricture when other studies are equivocal.